2021
DOI: 10.1097/eja.0000000000001462
|View full text |Cite
|
Sign up to set email alerts
|

For nasotracheal intubation, which nostril results in less epistaxis: right or left?

Abstract: BACKGROUND Nasotracheal intubation is usually required in patients undergoing oromaxillofacial, otolaryngological or plastic surgery to prevent the airway encroaching into the operating field. Epistaxis is the most common complication, but which nostril is associated with a lower incidence and severity of epistaxis is still unclear. OBJECTIVE When both nostrils are patent, to determine the preferred nostril for nasotracheal intubation under general anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The finding of the spur deriving from the nasal septum is around 1.2% [ 10 ]. The nasal spur can cause pain, particularly rhinogenic contact point ear pain; the latter is an otalgic pain with tinnitus caused by contact between the spur and the intranasal mucosal [ 11 ]. Tendentially, in the presence of a bone spur, an endoscopic operation can be carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of the spur deriving from the nasal septum is around 1.2% [ 10 ]. The nasal spur can cause pain, particularly rhinogenic contact point ear pain; the latter is an otalgic pain with tinnitus caused by contact between the spur and the intranasal mucosal [ 11 ]. Tendentially, in the presence of a bone spur, an endoscopic operation can be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The nasotracheal approach to intubation is never without risk or minor trauma. One of the most recurrent events is epistaxis, which is most noticeable if the procedure starts from the left nostril; the right nostril is less prone to epistaxis and demonstrates a faster access rate [ 11 ]. Intubation from the right nostril better respects the anatomy of the retropharyngeal wall when the tube is inserted [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epistaxis that occurs with a video stylet can lead to a blood-stained lens, which can obscure the field of view and lead to failed intubation. In two systematic reviews, nasotracheal intubation via the left nostril significantly increased the risk of epistaxis than via the right nostril [ 5 , 6 ]. It has been thought that the tube bevel’s orientation can impact nasotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus about which nostril is better for nasotracheal intubation, several studies found that the right nostril may be more suitable for laryngoscopic nasotracheal intubation [ 2 4 ]. Two systematic reviews showed that intubation via the right nostril is associated with faster intubation and lower incidence of epistaxis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epistaxis, which frequently appears with varying severity, is the most common complication of nasotracheal intubation. 2 Regarding predicting the tube advancement difficulty through the nasal passage, the general recommendation is to perform nasal endoscopy before intubation which is a time-consuming and equipment-requiring procedure. 3,4 The higher rate of success and the shorter operation time in surgeries have come to be achieved by the guidance of many radiological imaging devices, like ultrasonography (USG), magnetic resonance imaging (MRI), computed tomography (CT) imaging and others.…”
Section: Introductionmentioning
confidence: 99%